Electronic structure of multi-layered graphene oxide membrane moderately reduced in vacuum. (May 2022) - Fok, T.; Janulewicz, K.A.; Wachulak, P.; Bartnik, A.; Nasiłowska, B.; Kostecki, J.; Budner, B.; Fiedorowicz, H.; Djas, M.; Kuźmiuk, P.; Lawniczak-Jablonska, K.
Abstract: Graphene oxide (GO) has recently attracted more attention for its own physical and chemical properties regardless of being initially seen only as an ideal candidate for the production process of single/few graphene layers. One of the most interesting forms of this material is a multilayer structure, sometimes called graphene paper, with a thickness approaching a value up to a few micrometers. We present and discuss the results of investigation on electronic structure of such a thick material produced by the improved Hummer's method and deposited on a metallic mesh. The samples were investigated by near-edge X-ray absorption fine structure spectroscopy (NEXAFS) around the carbon absorption edge. The NEXAFS results are supplemented with the output of the X-ray photoelectron spectroscopy (XPS) analysis for C1 s and O1 s lines and with the micro-Raman spectroscopy. There are still some discrepancies concerning the electronic structure of graphene oxide (GO), especially, when many individual GO sheets are stacked together as in the case under consideration. The samples were heavily functionalized by oxidation (the presence of carbonyl, epoxy, and hydroxyl groups). There are indications that the prepared samples tended towards the turbostratic form of stacking when annealed in vacuum at moderate temperatures between 100 °C and 500 °C. These changes were observed in both π * and σ * resonance areas. Surprisingly, the features of the NEXAFS spectrum of both the annealed and non-annealed samples resemble reasonably the theoretically determined structure of the density of states (DOS) of monocrystalline carbon. It could suggest a strong "graphitisation" process already in the sample preparation phase. The observed increase in the sample amenability to the environmental water with annealing temperature is discussed briefly. The results also deliver a clear support for the claims of room-temperature metastability of multilayer GO. Highlights: The structure of the material formed from suspension shows many features of the turbostratic stacking. Multi-layer GO membrane cannot be fully freed from the functional groups by moderate annealing. Multi-layer GO membrane shows high susceptibility to the environmental humidity - the feature enhanced by annealing. Multi-layer GO membrane shows a metastable structural character.